3-D tomographic model inferred from broadband seismological data at Hengill geothermal field (Iceland) - Jousset, Philippe (Zenodo, 2008)
This report describes the processing carried out to retrieve data from the disks anddescribes algorithms used in order to extract significant information from data about theseismic activity at the Hengill geothermal field and the neighbouring volcanic complex. The data set consists of broadband seismological data form the IGET network andfrom 3 stations of the SIL network, allowing us a more accurate analysis of the seismicactivity within the area. We performed: • detection and classification of recorded seismicity • improvement of hypocenter locations and structural features of the geothermalsystem by tomography techniques ENGINE - FP6